2021
DOI: 10.3390/nano11092278
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Antioxidant Efficiency and Antibacterial Mechanism of Bitter Gourd Extract Stabilized Silver Nanoparticles

Abstract: In this study, we accentuate the facile and green synthesis of ecologically viable silver nanoparticles (AgNPs) using aqueous (A-BGE) and ethanolic (E-BGE) dried bitter gourd (Momordica charantia) fruit extract as reducing and capping agents. Although AgNPs synthesized using BGEs have been reported earlier in fundamental antimicrobial studies, the possible antioxidant activity, antibacterial efficacy against superbugs, and a potential antimicrobial mechanism are still lacking. The characterization of as-prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Compared to A-DE-AgNPs, using A-BL-AgNPs as an antibacterial reagent not only showed similar S. aureus (Gram-positive bacteria) killing activity but also exhibited twofold higher antimicrobial efficiency against Gram-negative bacteria. A-BL-AgNPs also showed a better antibacterial efficiency against the wild-type and two drug-resistant A. baumannii strains (MIC = 2 mg mL À1 ) than the bitter melon extract-mediated AgNPs from our previous report, 47 which might be due to the CGE-mediated AgNPs releasing more Ag + ions. Several plant extract mediated AgNPs against multi-drug resistant bacterial pathogens have been explored recently due to the widespread antibiotic resistance around the world.…”
Section: Njc Papermentioning
confidence: 65%
“…Compared to A-DE-AgNPs, using A-BL-AgNPs as an antibacterial reagent not only showed similar S. aureus (Gram-positive bacteria) killing activity but also exhibited twofold higher antimicrobial efficiency against Gram-negative bacteria. A-BL-AgNPs also showed a better antibacterial efficiency against the wild-type and two drug-resistant A. baumannii strains (MIC = 2 mg mL À1 ) than the bitter melon extract-mediated AgNPs from our previous report, 47 which might be due to the CGE-mediated AgNPs releasing more Ag + ions. Several plant extract mediated AgNPs against multi-drug resistant bacterial pathogens have been explored recently due to the widespread antibiotic resistance around the world.…”
Section: Njc Papermentioning
confidence: 65%
“…The most important antioxidant components are polyphenolic compounds (including flavonoids) that deactivate free radicals due to their hydrogen-donating ability. A linear relationship between the total phenolic and flavonoid content and antioxidant capacity has been reported in several literature publications [39][40][41].…”
Section: Discussionmentioning
confidence: 75%
“…AgNPs inhibited the growth of both tested Gram-negative and Gram-positive multi-drug-resistant (MDR) strains with MIC and MBC values ranging between 0.019–0.156 and 0.039–0.625 mg/mL, respectively. Moorthy et al (2021) produced AgNPs using aqueous and ethanolic bitter gourd ( M. charantia ) extracts (A-BG-AgNPs and E-BG-AgNPs, respectively) [ 152 ]. They found that E-BG-AgNPs were much smaller in size and showed greater agglomeration than the aqueous ones.…”
Section: Nanoparticlesmentioning
confidence: 99%